Comparison of clinical responses between 3-in-1 vaccine and 2-in-1 + 1 vaccine [Porcine reproductive and respiratory syndrome (PRRS), porcine circovirus type 2 (PCV2) and mycoplasma hyopneumoniae (SEP)] following vaccination of swine in Peninsular Malaysia - Ng, Li Kai. (2018)
Traditionally, monovalent vaccine is commonly practice in the swine industry. Manufactures are merging vaccines together to improve the practicality of vaccination to increase disease protection coverage as compared with single vaccine. However, combined vaccines might have higher interference among vaccine components as the amount of antigen increases. Therefore, the objective of this study is to compare the clinical responses berween 3-in-1 vaccine and 2-in-1 + 1 vaccine against Porcine Reproductive and Respiratory Syndrome (PRRS), Porcine Circovirus type 2 (PCV2) and Mycoplasma hyopneumoniae following vaccination of swine, in Peninsular Malaysia. The hypothesis of the study is there is no significant difference between clinical responses in both vaccination regime. A total of 160 piglets from 26 pens were divided into control [2-in-1 (PCV2 and M. hyopneumoniae), 1-in-1 (PRRS)] and treatment group [3-in-1 (PCV2, M.hyopneumoniae and PRRS)]. The piglets were vaccinated at 18 days old. The vaccination responses were monitored for 4 weeks post vaccination. The clinical responses after vaccination in terms of rectal temperature changes, adverse inflammatory signs at vaccination site and post-weaning average daily gain (ADG) were compared between the two groups. The results of both groups showed insignificant difference at p>0.05. There were no adverse inflammatory signs observed at vaccination site in both groups. This study suggested that piglets vaccinated with 3-in-1 vaccine did not show statistical difference while providing the convenience of a single which reduced labour cost, time and stress among the piglets as compared to separate vaccination with 2-in-1 + 1 vaccine.